2017
DOI: 10.1016/j.nicl.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive, multimodal analysis of cortical activity, blood volume and neurovascular coupling in infantile spasms using EEG-fNIRS monitoring

Abstract: Although infantile spasms can be caused by a variety of etiologies, the clinical features are stereotypical. The neuronal and vascular mechanisms that contribute to the emergence of infantile spasms are not well understood. We performed a multimodal study by simultaneously recording electroencephalogram and functional Near-infrared spectroscopy in an intentionally heterogeneous population of six children with spasms in clusters. Regardless of the etiology, spasms were accompanied by two phases of hemodynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(78 reference statements)
3
13
0
Order By: Relevance
“…The changes in HbO–HbR demonstrated by multidistance NIRS analysis support the idea that hemodynamic changes are the result of changes in the dynamics of cortical microvessels. The laser hemodynamic response supports pollution (or cross‐talk) from deeper structures that progressively disappear from deep to superficial layers (Bourel‐Ponchel et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The changes in HbO–HbR demonstrated by multidistance NIRS analysis support the idea that hemodynamic changes are the result of changes in the dynamics of cortical microvessels. The laser hemodynamic response supports pollution (or cross‐talk) from deeper structures that progressively disappear from deep to superficial layers (Bourel‐Ponchel et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…However, some studies did not observe typical NVC and many studies have reported negative NVC in response to exogenous stimulation (A. P. Born et al, ). Apart from the immaturity of intimate cellular mechanisms, these differences could also be due to the different strategies of the vascular system to respond to increased metabolic demand, depending on baseline status of the neuronal and hemodynamic system (Bourel‐Ponchel, Mahmoudzadeh, Delignières, Berquin, & Wallois, ). According to the classification based on hemodynamic response, averaging of the various responses will obviously modify the global averaged hemodynamic output comprising a mix of positive and negative CBF or CBV responses, resulting in the absence of a hemodynamic response observed in Subcondition A0 without taking into account the IBI or the direction of HbO and HbR changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations